NEUROBLASTOMA IN HORSESHOE KIDNEY - Nawaz, Gul; Muhammad, Shujah; Jamil, Muhammad Imran; Shohab, Durre; Khan, Iftikhar Ali; Khawaja, Muhammad Athar; Gulzar, Shahnawar; Akber, Mian Khalid; Khan, Ayaz; Hussain, Ijaz; et al. (Journal of Ayub Medical College Abbottabad, 2014)
Neuroblastoma is one of the commonest malignancy of childhood. Neuroblatoma in horseshoe kidney is an extremely rare condition. There is only one case of this tumour occurring in horseshoe kidney described in the literature. Recently we successfully treated a boy with neuroblastoma in horseshoe kidney. Keywords: Neuroblastoma, Horseshoe kidney